Putting Yourself on the Line: The Harms of Competition - Drissen, Yvette (2025)
Competition is a key element in the design of social institutions in contemporary liberal democracies. Competitive procedures for jobs, grants and university admissions can be considered ‘substantially engulfing’ since they provide access to important goods that everyone has reasons to want, such as financial security, the social bases of self-respect and education. While competition can have beneficial outcomes and can be a fair way of selecting meritorious candidates, this paper aims to identify the distinctive moral problems it raises by developing what we call a ‘Harm Account’ of competition. We argue that substantially engulfing competitions predictably lead to three types of harm: (1) substantial psychological and emotional costs; (2) substantial opportunity costs; and (3) estrangement. These harms provide strong pro tanto reasons against organizing substantially engulfing competitions for important goods. The weight of these reasons depends on the stakes and scope of the competition at hand.